Susceptibility of Ethiopian wheat varieties to granary weevil and rice weevil infestation at optimal and sub-optimal temperatures. (September 2019) - Kalsa, Karta Kaske; Subramanyam, Bhadriraju; Demissie, Girma; Mahroof, Rizana; Worku, Admasu; Gabbiye, Nigus; Workneh, Solomon; Abay, Fetien
Abstract: Integrating varietal resistance with temperature manipulation during storage may provide a better option for protection of stored grains and may decrease reliance on the use of synthetic chemicals. The current study was conducted to determine the susceptibility of different varieties of wheat seed to the infestation by the granary weevil, Sitophilus granarius (L.), and rice weevil, Sitophilus oryzae (L.), at optimal (30 °C) and sub-optimal (19 °C) temperatures. Kernels of six wheat varieties namely, Danda'a, Digalu, ET-13-A2, Kakaba, Millennium, and Pavon-76 were examined over a period of 90 d. Significant interactions were detected between wheat varieties and storage temperature for progeny emergence, percentage of insect damaged kernels, grain weight loss, and amount of powder produced per gram of wheat. Kernels of Danda'a, infested with S. oryzae at 30 °C exhibited significantly lower mean progeny counts (13.3 live insects), lower percentage of grain weight loss (4.2%) and insect-damaged kernels (6.4%), and powder production (1.5 mg/g). Kernel weight and hardness index were negatively associated with percentage of insect damaged kernels and grain weight loss. Kernel diameter was positively associated with both of percentage of insect damaged kernels and grain weight loss. Wheat varieties with high Zeleny sedimentation values had lower percentage of insect-damaged kernels and grain weight loss. These results indicated that kernel weight, hardness index, and protein content are predominant factors contributing to wheat resistance against S. granarius and S. oryzae . The varieties Millennium and Danda'a can be considered with other integrated pest management approaches to reduce stored grain losses of wheat in Ethiopia. Highlights: Integrating varieties with temperature can be used to protect stored wheat in Ethiopia. We studied responses different wheat varieties to the infestation by weevils at two temperatures. All varieties appeared susceptible to both S. granarius and S. oryzae at 30 °C. Kernel weight and hardness index were negatively correlated with percentage seed damage and weight loss. Wheat varieties with high protein sedimentation values had less percentage of seed damage and weight loss.